Functional Status, Anxiety, Cardiac Self-Efficacy, and Health Beliefs of Patients with Coronary Heart Disease - Hamid Allahverdipour; Mohammad AsghariJafarabadi; Rasoul Heshmati; Mina Hashemiparast (Tabriz University of Medical Sciences, 2013)
Background: Beliefs and emotions could effect on functional status, quality of life, and mortality amongst patients who are suffering coronary heart disease (CHD). Current study examined the role of anxiety: trait/ state, self-efficacy, health beliefs, and functional status among patient with history of CHD. Method: In this correlational study, 105 hospitalized and outpatients patients suffering CHD in Tehran Heart Center Hospital participated by using convenience sampling method in 2012. Cardiac self-efficacy, Seattle Angina, and research- designed health beliefs questionnaires were used to gather data. Results: The functional status in CHD patients showed significant relationships with gender, job, and type of medical insurance of the participants (All ps<0.05). In addition , perceived vulnerability to face again cardiac attack in the future, perceived severity of next cardiac attack, anxiety, state anxiety and trait anxiety (All ps<0.05) had significant and negative relationships with functional status. Conversely, the cardiac self-efficacy had a positive and significant relationship (P<0.001) with functional status. Conclusion: Psychological factors have important role in functional status and quality of life of patients who suffering CHD. Therefore, it is necessary to emphasize on supportive and complementary programs to promote Cardiac Rehabilitation Programs.